Analisis penerapan KUHP dan qanun jinayah Aceh nomor 6 tahun 2014 - Wolly Mistiar (Ruang Cendekia : Jurnal Pengabdian Kepada Masyarakat, 2022)
What was updated in the Codification of the Aceh Jinayah Qanun regarding the finger of seclusion and whether with the existence of a non-Muslim territorial principle, the punishment could be applied or not. One of these issues is regarding the granting of authority to violators of the jinayat law to vote. The purpose of the expected activity is to obtain results that can increase public knowledge and understanding about non-Muslim territories, and whether or not punishment can be applied. This year's Study Program-based community service activity program collaborates with the Sharia Court of Simeulue Regency and involves the people of Sinabang Village, East Simeulue District. The community service activity program carried out is legal counseling. This is related to the authority of the Sharia Court as one of the institutions that have the authority to settle cases in this field, Jarimah Khalwat in the territory of Aceh. International law, national or state law must guard the comfort and security of its territory from various violations and crimes that disturb the comfort of a country and the stability of the state towards its citizens. When a non-Muslim commits an act that is prohibited in an area where Islamic law applies, the non-Muslim can make a choice. This is felt to be unfair and inappropriate. Where the earth is stepped on there the sky is upheld. Moreover, the prohibition contained in the qanun jinayat is indeed prohibited in any religion.